2010
DOI: 10.1159/000322558
|View full text |Cite
|
Sign up to set email alerts
|

Basilar Artery Diameter Is a Potential Screening Tool for Fabry Disease in Young Stroke Patients

Abstract: Background: Fabry disease (FD) is a rare hereditary lysosomal storage disease that has been highlighted as a possible etiology of stroke at a young age. Enlarged basilar artery diameters (BADs) have been demonstrated in FD, and we hypothesize that they might be useful for the screening of FD in young stroke patients. The aim of this study was to compare BADs of young stroke patients without FD to those of FD patients and of healthy age-matched controls. Methods: BADs were measured using MR angiography in 3 age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 46 publications
(36 reference statements)
5
37
1
2
Order By: Relevance
“…Nonetheless, the characterization of the evolution of basilar artery changes in FD remains rather elusive. Azevedo et al 19 found increased basilar artery diameter values in older patients with FD, whereas Fellgiebel et al 14,15 and Uçeyler et al 16 found no association with age. The present study showed that the basilar artery diameter increases significantly with age in the female subgroup, whereas male patients with FD and both male and female control patients do not change significantly over time.…”
Section: Evolution Of Basilar Artery Changesmentioning
confidence: 98%
See 2 more Smart Citations
“…Nonetheless, the characterization of the evolution of basilar artery changes in FD remains rather elusive. Azevedo et al 19 found increased basilar artery diameter values in older patients with FD, whereas Fellgiebel et al 14,15 and Uçeyler et al 16 found no association with age. The present study showed that the basilar artery diameter increases significantly with age in the female subgroup, whereas male patients with FD and both male and female control patients do not change significantly over time.…”
Section: Evolution Of Basilar Artery Changesmentioning
confidence: 98%
“…[9][10][11][12][13] A few studies applied a semiquantitative or quantitative approach with MRA 3D reconstructions (2 studies with 1.5T and 1 with 3T scanner), [14][15][16]19 T2 axial images (van der Tol L, personal communication), either T2 axial images or MRA, 17 or axial partitions of MRA (present study). Despite different methods, sequences, and scanners used for the measurement and the different ways to present study findings (different patient subgrouping, mean or median value, etc), all studies consistently showed the increase of the basilar artery diameter in patients with FD compared with control patients (On-line Table 2).…”
Section: Basilar Artery Diameter Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertebrobasilar dolichoectasia seems to be the earliest finding in relation to cerebrovascular damage in patients with FD (personal observation in press). Certain authors have demonstrated that measuring the diameter of the basilar artery may be a useful monitoring tool, as this has been the only parameter which separated general population with a stroke (group control) from patients with FD and stroke (Fellgiebel et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Ряд исследований показал, что изме-нение диаметра основной артерии является инфор-мативным маркером данной болезни [82]. Имеются сведения о раннем развитии атеросклероза и высо-ком уровне гомоцистеина у пациентов с болезнью Фабри [83].…”
Section: врожденные и приобретенные нарушения метаболизма с преимущесunclassified